Principles Of Russian Orography In The Practical Course Of Russian As A Foreign Language - Rakhmanova G.G. (Zien Journals, 2024)
This article describes the basic principles of Russian language orthography, creating a set of tasks and exercises for practicing orthographic norms in Russian language classes as a foreign language
Keywords: orthography; phoneme; learning